Fatigue Strength of Nodular Cast Iron with Different Surface Conditions under Bending Loading - Marian Kokavec; Radomila Konecna; Gianni Nicoletto (Communications - Scientific letters of the University of Zilina, 2012)
The aim of this study is to evaluate the effects of surface conditions on the fatigue life of nodular cast iron under cyclic plane bending where the maximum stress is reached at the surface of interest. In order to evaluate the effect of surface conditions, fatigue tests were carried out on five sets of specimens with different surfaces. The surface conditions were as-cast, sand blasted, fine ground, nitrided and carbonitrided. The results show differences in fatigue strength, which are associated with the surface conditions. The characteristics of the surface layers in the different test specimens were examined by metallography. The fracture surfaces were fractographically analyzed to find places of fatigue crack initiation and to explain different fatigue life.